Person Prefixes in Pima Bajo and Analytical Decisions - Estrada, Zarina; Steele, Susan (International journal of American linguistics, 1999)
Insights from processual theories of morphology, with focus on the function of morphology to introduce information that is interpreted by the syntax, are applied to an analysis of the homophonous sets of possessive, object, & subject person markers in Pima Bajo, a Tepiman (Uto-Aztecan) language of northern Mexico. It is argued that the Pima Bajo person markers are phonological reflexes of a single operation that contributes a person value to the feature structure of a word; the subcategorization feature determines the interpretation of the person value as possessive if the feature is null, objective if it allows the object's value to be independent of other elements, & subjective in all other cases. The person markers are therefore not syntactic elements but values introduced to different types of signs. 1 Appendix, 16 References. J. Hitchcock